Investment Attractiveness of "Green" Financial Instruments - Shaydurova, Alina; Panova, Svetlana; Fedosova, Raisa; Zlotnikova, Galina (Journal of Reviews on Global Economics, 2018)
Nowadays the largest institutional investors and exchange-traded funds invest a great part of their portfolio in the assets connected with environmental-friendly activities. "Green" financial instruments can accumulate resources for climate change adaptation and infrastructure projects in areas such as renewable energy generation, energy effectiveness, clean water, low-carbon transport, etc. Thus, the concept of sustainable development not only pay attention to the climate risks but also creates new factor of investment attractiveness and makes the investment process more conscious and less speculative. Governments are also interested in the development of "green" instruments as their can play a significant role in the adaptation to the climate change and movement of the capital flows from the financial sector into the ecological industrial projects. The study shows that the necessary funds can be accumulated successfully due to defensive character of "green" instruments and their sustainability to the market shocks.